Experiment and time‐varying characteristics of steel corrosion in magnesium oxychloride cement. (13th September 2020) - Gong, Wei; Wang, Nan; Zhang, Na; Chen, Guangfeng
Abstract: The steel corrosion in magnesium oxychloride cement (MOC) restrains the application and popularization of MOC products. However, MOC is a green cementitious material. Therefore, it is necessary to solve the steel corrosion in MOC. Aiming at this issue, firstly, the Stern–Geary constant ( B ) applied to the steel corrosion in MOC was calculated and verified. Secondly, the influence of different steel and mineral admixtures on the steel corrosion in MOC was studied by electrochemical method. Thirdly, the time‐varying models of steel corrosion were given. Fourthly, the life of the steel‐MOC system was calculated based on the time‐varying model. Finally, the time‐varying characteristics of steel corrosion in MOC was proposed. The results show that B of 25 mV is suitable for the corroded steel, whereas B of 40 mV is appropriate for uncorroded steel, in MOC. In addition, the type of steel has a significant effect on steel corrosion in MOC. The anticorrosive effect of metakaolin is less than that of fly ash. The anticorrosive effect of MOC with single admixture is better than that with compound admixture. Besides, the development process of steel corrosion in MOC can be divided into three stages: the descending phase conforming to the exponential time‐varying model in the early stage, the ascending phase conforming to the logarithmic time‐varying model in the middle stage, and the descending phase conforming to the exponential time‐varying model in later stage.